TELAAH AKSIOLOGI DAN EPISTIMOLOGI ILMU TERHADAP PSIKOLOGI ISLAM - Nurhayani Nurhayani (JURNAL TARBIYAH, 2016)
Science has given signs of dehumanation even it can change human’s self. In other words, science is not as tools to help human in reaching their purpose of life, even create their future. Facing this fact, science that has purpose to learn nature as it is, it begin to ask about for what science will use? How is the authority of science research? In this occasion, the responsibility and integrity of scientist is tested. Study of axiology to psychology can be understood well if  we use theory of morality. According to theory of morality, science should be purposed for human kindness without humaliating the  human values  and changing the human essence. The truth that can reached by philosopy and science  will never end and go on processing and become. And those are signs that  human, his thinking and creation are relative. But the truth consider identical to The Maker of truth. Keywords: Axiology, Epistimologi, Islamic Psychology